BASIC PSYCHOLOGICAL NEEDS, MOTIVATIONAL ORIENTATIONS, EFFORT, AND VOCABULARY KNOWLEDGE: A COMPREHENSIVE MODEL - Alamer, Abdullah (Studies in second language acquisition, 2022)
This study examined an integrated process model of second language motivation based on the framework of self-determination theory (SDT). Specifically, this research investigated the extent to which satisfying basic psychological needs (BPN) are related to SDT orientations and, in turn, to the effort expended and how these factors relate collectively to vocabulary knowledge. Revised scales assessing students’ BPN (the Basic Psychological Needs of Second Language Scale) and SDT orientations (the Self-Determination Theory of Second Language Scale) were considered and tested using a higher-order confirmatory factor analysis solution. The results of the structural model showed that BPN were only directly related to vocabulary knowledge, which indicated their direct importance for the attainment of the vocabulary. No other indirect effects through SDT orientations or effort were identified. Nonetheless, SDT orientations were both directly and indirectly linked to vocabulary knowledge over and above the role of expended effort. The results elucidated motivational pathways that yielded pedagogical implications for language learning.